2013
DOI: 10.3233/wor-131741
|View full text |Cite
|
Sign up to set email alerts
|

The standpoint of persons with hearing loss on work disparities and workplace accommodations

Abstract: OBJECTIVES:The perspectives of persons who live and work with hearing loss were sought to examine workplace accommodation challenges and strategies. PARTICIPANTS: A convenience sample of seven older adults with hearing loss participated in in-depth interviews. METHODS: A systematic grounded theory approach informed the study design and analysis. Categories of facilitators and challenges in the data were identified through axial coding and clustering. Core categories of social processes emerged through constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…The lack of access to adequate service providers, particularly, services with audiological knowhow, was a major barrier to sustainable participation, thus confirming previous research [22]. Danermark and Gellerstedt [27] found in a cross-sectional study that employees with hearing impairments reported higher demands and lower control in stressful work than their normalhearing peers, and the authors claimed a need for more intense aural rehabilitation.…”
Section: The Role Of Aural Rehabilitation In Sustainable Participationsupporting
confidence: 75%
See 1 more Smart Citation
“…The lack of access to adequate service providers, particularly, services with audiological knowhow, was a major barrier to sustainable participation, thus confirming previous research [22]. Danermark and Gellerstedt [27] found in a cross-sectional study that employees with hearing impairments reported higher demands and lower control in stressful work than their normalhearing peers, and the authors claimed a need for more intense aural rehabilitation.…”
Section: The Role Of Aural Rehabilitation In Sustainable Participationsupporting
confidence: 75%
“…Such knowledge tended to be a key to self-efficacy, but was frequently accessed coincidentally. A lack of access to knowledge of how to enable efficient work accommodation processes in employees with hearing impairments has been found previously [22]. Thus, to avoid exhaustion it seems pivotal to access knowledge earlier and thus limit the time spent in the pre-acknowledgement phase.…”
Section: Discussionmentioning
confidence: 94%
“…Employees with hearing impairments have been found to use a variety of strategies to sustain work performance [15]. The strategies used were self-accommodation, self-advocacy, self-management, and lobbying.…”
Section: Introductionmentioning
confidence: 99%
“…Persons with disabilities employ various strategies to be successful in the workplace. In some cases, persons with disabilities try to cover up the disabilities to maintain the status quo in the workplace (Baldridge & Kulkarni, 2017;Shaw, Tetlaff, Jennings, & Southall, 2013). Baldridge and Kulkarni (2017) discuss how persons with disabilities maintain careers and achieve success following the onset of the disabilities by modifying job roles and relying on support from social networks.…”
mentioning
confidence: 99%
“…Through self-accommodation, persons with disabilities develop their own strategies for overcoming their disabilities. Lobbying involves working outside the organization to encourage change (Shaw et al, 2013). Lysaght, Fabrigar, Larmour-Trode, Stewart, and Friesen (2012) report that social To take full advantage of the abilities of persons with disabilities, organizations need to engage, empower, and embrace the employees in the workplace.…”
mentioning
confidence: 99%